The Influence of Artificial Intelligence Service Quality and Customers Trust on Customers Loyality Bank BRI Larompong Unit - Ramadhani, Rezky; Haedar, Haedar; Rismawati, Rismawati; Wagay, Javaid Ahmad (PT. EQUATOR SINAR AKADEMIA, 2026)
This study aims to analyze the influence of Artificial Intelligence (AI) service quality and customer trust on customer loyalty at Bank BRI Larompong Unit. I examine how AI-based service technologies, including mobile banking features, shape customer behavior in maintaining long-term relationships with the bank. The study uses a quantitative research design with multiple linear regression analysis and involves 300 respondents selected using Slovin’s formula. I collect data through questionnaires that measure customer perceptions of AI service quality, trust, and loyalty.The results show that both AI service quality and customer trust exert a positive and significant influence on customer loyalty. Improvements in system reliability, information accuracy, response speed, and data security strengthen customer trust and increase their likelihood of continuing to use AI-based banking services. The findings also indicate that customer trust has a stronger effect on loyalty than AI service quality..This study presents originality by focusing on the adoption of AI technology in a regional banking environment, an area that remains underexplored in existing literature.The practical implications suggest that Bank BRI Larompong Unit needs to continuously strengthen its AI systems by improving usability, personalizing services, increasing system transparency, and enhancing data security. Strengthening these elements is essential to reinforce customer trust and maintain loyalty in an increasingly competitive digital banking landscape.